(3cJGH aj GdWdhY hGdZQhHs - (3GhWhdhbSs
(3ChdgG (B:s
(3jbGd dHYV WdhYGJ GdchGcH hZQhHgG hNUhUkG GdKhGHJ CfgG NajI hdHYVgG EfgG XGgQI s
(3BNQgG (B:s
(3hPdc BNQ GdebGdI GdKGfjI hHJeGegG Je cJGH ChWhdhbS ai GdWdhY hGdZQhH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3GdfSNI HgG MhGTs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1435s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs